DESIGNING STT PLATFORM BASED ON PERCEIVED VALUE ON SMART TOURISM - Lukmanul Hakim; Isnandar Agus; Faurani Santi Singagerda; Firmansyah Yunialfi Alfian (Universitas Dharma Wacana, 2022)
Our article investigated how to create a design for smart tourism applications that focused on the values felt by tourists, specifically on the valuable experiences encountered by tourists during destinations such as accessibility, amenities, available packages, activities, and additional services, in order to assess the successful management of a tourist destination. Whereas the methodology applied in this research is Design Science Research (DSR), which is used to overcome a problem by designing a tool to address the issue, the major challenge that is frequently experienced by visitors in tourism studies is the convenience and completeness of information about tourist destinations. The theoretical contribution of the research might provide to the capacity in the study of tourist behavior, which is associated primarily with tourist satisfaction with a specific tourist destination based on previous experience and information. Whereas practically, the research will assist tourism managers in developing architectural designs of service tools to help tourist destination management in making decisions based on the requirements and preferences of tourists during their visit. Based on our findings, we recommend that tourist destinations should create dynamic platforms that mediate STT in order to respond to tourist demands. Tourists will appreciate their vacation more because the travel service experience is improved. Thus, providing information more accessible, constructing integrated information systems, and creating a technologically friendly environment would increase tourist participation and actually contribute to the overall travel experience.